1998
DOI: 10.1007/s002030050645
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-associated redox activities in Thermotoga neapolitana

Abstract: Elemental sulfur reduction by the hyperthermophilic bacterium Thermotoga neapolitana provides an alternative to hydrogen evolution during fermentation. Electrons are transferred from reduced cofactors (ferredoxin and NADH) to sulfur by a series of unknown steps. One enzyme that may be involved is an NADH:methyl viologen oxidoreductase (NMOR), an activity that in other fermenting organisms is associated with NADH:ferredoxin oxidoreductase. We found that 83% of NMOR activity was contained in the pellet fraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…This operon may encode a membrane-bound NAD:methyl viologen oxidoreductase like that observed in Tt. neapolitana (15). That enzyme did not use ferredoxin as a substrate, so the cofactor naturally paired with NAD under physiological conditions is unknown.…”
Section: Resultsmentioning
confidence: 99%
“…This operon may encode a membrane-bound NAD:methyl viologen oxidoreductase like that observed in Tt. neapolitana (15). That enzyme did not use ferredoxin as a substrate, so the cofactor naturally paired with NAD under physiological conditions is unknown.…”
Section: Resultsmentioning
confidence: 99%
“…These high yields and the depletion of headspace oxygen suggested that T. neapolitana utilizes oxygen for a more energy-efficient catabolic process. Extra-cytoplasmic oxygen-resistant hydrogenase activity has been detected in T. neapolitana [37], but the physiological role is unknown and H 2 -evolving hydrogenases are generally cytoplasmic [38]. Structural modelling of the [FeFe] hydrogenase α subunits suggests that the catalytic site of T. neapolitana’s enzyme may be less accessible to oxygen than T. maritima’s enzyme, accounting for increased resistance to inactivation [39].…”
Section: Formation Of Molecular H2 By Carbohydrate Fermentation Bymentioning
confidence: 99%
“…An O 2 insensitive hydrogenase has been described in T. neapolitana (Käslin et al 1998), which may explain why microaerobic H 2 production could take place in this bacterium. Since high H 2 yields are important for the development of microbial derived H 2 as a sustainable source of 'green' energy, we have tested the hypothesis that microaerobic metabolism increase the yield of H 2 from T. neapolitana (Van Ooteghem et al 2002 by investigating the conversion of glucose and generation of H 2 in anaerobic and microaerobic cultures of this bacterium.…”
Section: Introductionmentioning
confidence: 98%